Evaluation of DNA levels recovered from forensic bone samples through the optimization of a semi-automated extraction method. Issue 1 (December 2019) - Caldeira, M.J.; Bento, A.M.; Gouveia, N.; Brito, P.; Porto, M.J.
Abstract: DNA was extracted from eleven bone samples using PrepFiler Express BTA™ Forensic DNA Extraction kit with AutoMate Express™ Forensic DNA Extraction System with 20 and 50 μL of elution volume. The objective was to compare extraction efficiency with different elution volumes, evaluating DNA recovery, profile quality and observing if sample concentration alters the degradation index (DI) and the presence of inhibitors. The analyzed samples showed increased DNA levels with the elution volume of 20 μL, and the inhibition values did not change among the protocols, however some changes in the DI were observed. Undesirably, for low DNA concentrations, the 20 μL protocol demands more extractions per sample. This 20 μL method proved to be useful for difficult samples with low levels of DNA and high degradation, being able to increase DNA concentration and obtain genetic profiles with higher quality compared to the protocol in use, increasing the efficiency of analysis, important in cases of disaster victim identification (DVI).